The Students’ Ability on Identifying Adverbs in Writing Descriptive Text - Jessika Maria Sitompul; Resperdiana Purba; Sondang Mawarni Simanjuntak; Ernika Sitorus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the extent to which students' ability to apply adverbs to stories using descriptive text as the basis for learning English at SMA Puteri Sion Medan. The method used in this research is the descriptive qualitative method. Researchers made observations at school, then gave tests and interviews to students as data collection instruments needed in this study. The results of research that researchers have obtained show that most students can only understand adverbs of time and place, while other adverbs are still rarely used. In conclusion, the ability of Puteri Sion Medan high school students to write descriptive text using the adverb type is in a good category. Keywords: Adverbs, Descriptive Text, Identifying, Writing